Work Roll Speed Drop Compensation for Hot Strip Mills Reduces Drivetrain Wear and Increases Strip Quality - Löhe, Klaus; Reinhard, Johannes; Petrasch, Niklas; Kallabis, Sebastian; Graichen, Knut; Mucha, Martin (AISTech 2024 — Proceedings of the Iron & Steel Technology Conference, 2024)
Threading is a critical point in hot rolling. If the material hits the work rolls, a high rolling torque suddenly occurs resulting in a work roll speed drop. This is reflected in the thickness and width of the finished strip. In addition, the increase in torque leads to a high load on the drive train, i.e. the transmission and drive. This paper illustrates a recently presented method for compensation of the load torque at the point of threading. This model-based process enables a significant reduction in the speed drop and the torque peak that occurs. An overview of the current developments of the Speed Drop Compensation in the hot strip mill no. 1 of thyssenkrupp Steel Europe in Duisburg, Germany, is given.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Drive Train; Hot Rolling; Rolling Torque; Speed Control; Threadin Speed Drop; Torque Amplification Factor